Peer supervision in coaching and mentoring : a versatile guide for reflective practice - Turner, Tammy (Master certified coach); Lucas, Michelle; Whitaker, Carol (Executive coaching consultant) (Routledge, 2018)
Supervision is increasingly required for a coach's and a mentor's professional development, and engaging in reflective practice with peers can be a valuable way of meeting these needs. Peer supervision brings unique challenges though, including the possibility of collusion or stagnating at a shared developmental level. This book is written by practicing professional supervisors who engage in peer supervision themselves and train communities of coaches and mentors. It guides practitioners to develop and integrate their range of individual and group reflective practice activities alongside professional supervision. It draws upon essential theory and methodology, explores challenges and ethical dilemmas faced within peer supervision, and provides concrete guidance, useful techniques and helpful templates. This practical guide will be vital reading for individual coaching and mentoring practitioners and peer learning groups including within communities, universities and/or training programs. It will also support professional supervisors and organizations developing coaching cultures. 1. What is Peer Supervision? 2. Peer Supervision between Individuals 3. Peer Supervision in a Group 4. The Importance of Contracting 5. Ethics: The Elephant in the Room 6. Coaching and Mentoring Dilemmas 7. Managing the Pitfalls 8. When Should You Access Professional Supervision? 9. Taking Action 10. Looking Forward.